Paclitaxel blocks Th2-mediated TGF-β activation in Schistosoma mansoni-induced pulmonary hypertension. (December 2018) - Kassa, Biruk; Mickael, Claudia; Kumar, Rahul; Sanders, Linda; Koyanagi, Dan; Hernandez-Saavedra, Daniel; Tuder, Rubin M.; Graham, Brian B.
Schistosomiasis is a leading cause of pulmonary hypertension (PH) worldwide. Recent studies reveal that the type-2 immune cytokines IL-4 and IL-13, as well as consequent activation of TGF-β, are key factors in the pathogenesis of Schistosoma -PH. Paclitaxel has been reported to act as an adjuvant for Th2 inflammation while downregulating TGF-β activation. Moreover, paclitaxel blocks PH in monocrotaline and SU5416-hypoxia models. We hypothesized that paclitaxel would augment Th2 inflammation while blocking TGF-β activation and PH after schistosomiasis exposure. Wild-type mice (C57BL6/J; 6/group) were intraperitoneally (IP) sensitized and then intravenously (IV) challenged with Schistosoma mansoni eggs. One day after IV egg challenge, the mice were treated with a single IP dose of 25 mg/kg paclitaxel or vehicle. Right ventricular (RV) catheterization was performed and granuloma volumes and vascular remodeling were quantified. Lung cytokines were quantified by ELISA and reverse transcription polymerase chain reaction, and the quantity of active TGF-β was determined using a cell reporter line. We also investigated hypoxia-induced PH. Paclitaxel treatment significantly protected mice from Schistosoma -PH, with decreased RV systolic pressure ( P  = 0.005) and pulmonary vascular media thickness. Inflammation was significantly suppressed, contrary to our hypothesis, with decreased IL-4 and IL-13 levels, smaller granulomas, and less active TGF-β following paclitaxel treatment. There was no change in IFN-γ or FoxO1 or FoxO3 expression. Paclitaxel did not suppress chronic hypoxia-induced PH, which is also TGF-β-driven but independent of type-2 immunity. Paclitaxel protects against Schistosoma -induced PH in mice, although by blocking proximate Th2 inflammation rather than suppressing distal TGF-β activation.